Crop Output Projections for States By Agro-Climatic Sub Regions (Based on an Inter-Regional Area Allocation Model - Planning Commission (Planning Commission, 1994)
The Agro-climatic Regional Planning Project (ACRP) of the Planning Commission was initiated with a view to provide technical and scientific inputs for the Agriculture & Allied sectors during the VIIIth Plan. The project launched in mid 1988 has delineated the country into Agro-Climatic regions, after examining earlier attempts at regionalisation of the country by various scholars/expert bodies, the National Commission on Agriculture and the Indian Council of Agricultural Research (ICAR). This approach marks a departure from the sectoral approach in agricultural planning so far practised in the country, to a more holistic approach. The ACRP recognizes in an explicit manner the nature of the local resource endowments and constraints of the agro-climatically homogenous regions, which in most cases cut across the states. This concept gives greater consideration to the inherent commonality of the basic agro-metereological features and water resources in the agro-climatic regions, which are recognised as more appropriate units of planning, than the states.
Agro-Climatic Regional Planning Unit Planning Commission
Agro-Climatic Regional Planning Unit Planning Commission